Lactic acid bacteria: little helpers for many human tasks. Issue 2 (26th July 2021) - Sauer, Michael; Han, Nam Soo
Abstract: Lactic acid bacteria (LAB) are a group of highly specialised bacteria specifically adapted to a diverse range of habitats. They are found in the gut of humans and other animals, in many food fermentations, and on plants. Their natural specialisation in close relation to human activities make them particularly interesting from an industrial point of view. They are relevant not only for traditional food fermentations, but also as probiotics, potential therapeutics and cell factories for the production of many different products. Many new tools and methods are being developed to analyse and modify these microorganisms. This review shall give an overview highlighting some of the most striking characteristics of lactic acid bacteria and our approaches to harness their potential in many respects – from home made food to industrial chemical production, from probiotic activities to the most modern cancer treatments and vaccines.